Comparing schizophrenia symptoms in the Iban of Sarawak with other populations to elucidate clinical heterogeneity. (22nd August 2013) - McLean, Duncan; Barrett, Robert; Loa, Peter; Thara, Rangaswamy; John, Sujit; McGrath, John; Gratten, Jake; Mowry, Bryan
Abstract Introduction The symptom profile of schizophrenia can vary between ethnic groups. We explored selected symptom variables previously reported to be characteristic of schizophrenia in the Iban of Sarawak in transethnic populations from Australia, India, and Sarawak, Malaysia. We tested site differences to confirm previous research, and to explore implications of differences across populations for future investigations. Methods We recruited schizophrenia samples in Australia (n = 609), India (n = 310) and Sarawak (n = 205) primarily for the purposes of genetic studies. We analyzed seven identified variables and their relationship to site using logistic regression, including: global delusions, bizarre delusions, thought broadcast/insertion/withdrawal delusions, global hallucinations, auditory hallucinations, disorganized behavior, and prodromal duration. Results We identified a distinct symptom profile in our Sarawak sample. Specifically, the Iban exhibit: low frequency of thought broadcast/insertion/withdrawal delusions, high frequency of auditory hallucinations and disorganized behavior, with a comparatively short prodrome when compared with Australian and Indian populations. Discussion Understanding between‐site variation in symptom profile may complement future transethnic genetic studies, and provide important clues as to the nature of differing schizophrenia expression across ethnically distinct groups. A comprehensive approach to subtyping schizophrenia is warranted, utilizing comprehensively ascertained transethnic samples to inform both schizophrenia genetics and nosology.